Impacts of the Fight against Corruption by the Economic and Financial Crimes Commission in Promoting Good Governance and Accountability in Nigeria - C, Ndukwe; David, Ogo; Iroko, Nwuzor (Journal of Public Policy and Administration, 2023)
Purpose: This study investigated the impact of the fight against corruption by the EFCC in promoting good governance and accountability in the current administration of president Muhammadu Buhari. Specifically the paper sought to examine the extent to which the fight against corruption by the EFCC have promoted good governance and accountability in Nigeria today. Methodology: The methodology adopted is qualitative method of data collection and analysis where some informants with an experience and classified information on the subject matter were consulted for interview. The paper adopted Richard A Joseph (1996) Prebendalism theory on corruption. The data obtained was interpreted for analysis and findings. Findings: The paper discovered that as laudable as the intentions and effort of the government to curb corruption through the EFCC and laws, they have left much to be desired. Infact the fight against corruption by the EFCC are of limited value because they fail to take into account much of the dymanics that support corruption making people now regard the EFCC as a tool to fight political enemies of the current administration. Unique Contribution to Theory, Practice and Policy: The paper therefore recommends among others the need for greater transparency by the EFCC in combating corruption if its effort must promote good governance and accountability in Nigeria